Kajian Pusat Pertumbuhan Ekonomi Sektor Pertanian Kabupaten Hulu Sungai Tengah - Rum Van Royensyah; Ilman Safitri; Heldawati; Dewi Susanti (Rawa Sains: Jurnal Sains STIPER Amuntai, 2025)
Determining growth centers for local governments is very important, in order to make it easier to accelerate regional development. The more developed the growth center, the more developed the hinterland or supporting areas will be. The purpose of this research is to find out which sub-districts are the centers of economic growth, how much interaction occurs between sub-districts that act as growth centers with surrounding areas / sub-districts, the position of the economy in each economic sector and to find out the leading sectors in Hulu Sungai Tengah Regency. There are 11 sub-districts in Hulu Sungai Tengah Regency. This research is a type of quantitative descriptive research and uses secondary data sourced from books published by BPS Hulu Sungai Tengah Regency. This research uses Scalogram Analysis, Interaction/Gravity Analysis, Klassen Typology and LQ (Location Quotient). The results showed that in 2020 there were four sub-districts that had hierarchy I and hierarchy II so that they became growth center sub-districts, these sub-districts were Barabai, Haruyan, Pandawan and Batang Alai Selatan. The level of interaction between the growth center sub-districts and their surrounding sub-districts varies. Based on Klassen's typology analysis, the agriculture, forestry and fisheries sector is in Quadrant 1, which indicates that it is a developed and rapidly growing sector. The results of the LQ (Location Quotient) analysis show that the agriculture, forestry and fisheries sector (LQ = 1.83) is one of the leading sectors in Hulu Sungai Tengah Regency.